Intervensi Mental-Ku sebagai Sarana Peningkatan Self Efficacy dan Menajemen Stress pada Lansia Desa Grogol, Kec. Sawoo, Kab. Ponorogo - Kusumawardani, Winda; Putri, Berliana Devianti; Belqis, Belqis; Sari, Narta Nikita; Meilani, Estu; Putri, Inviana Agustin Dima (Universitas Baiturrahim, 2026)
Mental health among the elderly is an essential aspect that is often overlooked due to changes in social roles, loneliness, and decreased productivity. This condition is also found among the elderly in Grogol Village, Sawoo District, Ponorogo Regency. This community service activity aimed to improve the knowledge and stress management skills of the elderly through the “Intervensi Mental-KU” program. The methods used included interactive counseling, Brain Gym exercises, and relaxation practices using easily accessible audiovisual media. A total of 70 participants took part in the activity, with pre-test and post-test evaluations conducted to measure changes in knowledge and stress management abilities. The results showed a significant improvement, where the “good” category increased from 11.4% to 61.4%, while the “poor” category decreased from 42.9% to 2.9%. This program effectively enhanced awareness, motivation, and psychological well-being among participants. This program can serve as a sustainable community-based model for improving mental health and quality of life among the elderly